Presentations for Deepening Social Protection Systems: Enhancing livelihoods and health in Ethiopia - Alderman, Harold; Gilligan, Daniel O.; Hidrobo, Melissa; Leight, Jessica; Mulford, Michael; Tambet, Heleene; Mamo, Tigist (International Food Policy Research Institute, 2024)
Twenty years after the establishment of Ethiopia’s Productive Safety Net Program (PSNP), a major social protection system, the country’s government, donors, and other stakeholders are implementing multidimensional graduation model programs that are designed to complement the PSNP’s monthly food and cash transfers. Graduation models include multiple interventions such as large asset or lump-sum transfers, training, savings promotion, and other forms of nutrition, health, or psychosocial support. These models aim to move beyond cash or food transfers to ensure minimum consumption levels and address the multiple challenges that can trap poor households in poverty.